Investigating the effectiveness of three school based interventions for preventing psychotic experiences over a year period: a secondary data analysis study of a randomized control trial - Staines, Lorna; Healy, Colm; Corcoran, Paul; Keeley, Helen; Coughlan, Helen; McMahon, Elaine; Cotter, Pádraig; Cotter, David; Kelleher, Ian; Wasserman, Camilla; Brunner, Romuald; Kaess, Michael; et al. (BMC public health, 2023)
Psychotic experiences (PEs) are associated with increased risk of later mental disorders and so could be valuable in prevention studies. However, to date few intervention studies have examined PEs. Given this lack of evidence, in the current study a secondary data analysis was conducted on a clustered-randomized control trial (RCT) of 3 school based interventions to reduce suicidal behaviour, to investigate if these may reduce rates of PEs, and prevent PE, at 3-month and 1-year follow-up.